Análisis de las nuevas estrategias publicitarias que utiliza la cervecería nacional a partir de la aplicación de la Ley Orgánica de comunicación del año 2013 - Salazar Mesías, Carlos Julio (2016)
The following research project presents the analysis of the advertising strategies used by the Cervecería Nacional to publicize its product to its habitual consumers. A little is said about its history as it was born and developed over the years. What he had to face in regards to his publicity when creating the Organic Law of Communication of the year 2013, which regulates certain media in terms of advertising alcoholic beverages in moderation….